Monitoring of changes in selenium concentration in goat milk during short-term supplementation of various forms of selenium - Pechova, Alena; Misurova, Lubica; Pavlata, Leos; Dvorak, Rudolf (Biological trace element research, 2008)
The goal of the experiment was to monitor the changes in the selenium concentration in goat milk during short-term oral supplementation of three different forms of selenium. The experiment involved 24 lactating goats of white shorthaired breed. Group C was the control; group S received selenium in the form of selenium-enriched yeast, group L in the form of lactate, and group B in the form of proteinate. Individual selenium preparations were administered individually orally in 250 microg Se dose per animal for 20 days. After the beginning of selenium supplementation, the selenium concentration in milk during the first 5 days grew gradually in group S. Between days 7 and 20 of Se supplementation, the mean Se concentrations in milk in groups were 12.53 +/- 3.69 microg l(-1) (C), 25.90 +/- 6.30 microg l(-1) (S), 13.14 +/- 3.54 microg l(-1) (L), 11.70 +/- 3.69 microg l(-1) (B). Differences between group S and other groups (C, B, L) were highly significant (p < 0.0001). Based on our results, selenium in the form of lactate and proteinate was excreted into the milk similarly, but selenium in the form of yeast, which contains high amount of selenomethionine, was excreted by milk in the highest amounts.
Keywords: mléko; Dietary Supplements; zvířata; kozy; ženské pohlaví; selen; Lactation; Time Factors; kvasinky; selenomethionin; Selenium; Female; Goats; Milk; Yeasts; Lactic Acid; kyselina mléčná; Animals; potravní doplňky; laktace; Selenomethionine; časové faktory